Exploring Early Graders Teachers’ Perception of Teaching in Inclusive Classrooms: A Case Study of Private Schools, Karachi - Sohail, Muskan; Shaikh, Rabia (JECCE, 2025)
This qualitative study explores the perceptions of kindergarten II teachers regarding inclusive classrooms teaching in private schools of Karachi. Data were collected through semi-structured interview with six teachers selected through purposive sampling. Thematic Analysis was used to analyse the data. Findings revealed that teachers generally hold positive attitude towards inclusive education; however, they face challenges such as lack of training, insufficient resources and limited institutional support. The study highlights the need for continuous professional development, improved resource allocation, and stronger administrative support to enhance inclusive practices. The finding provides useful insight for policymakers and school administrators to strengthen inclusive education in private schools.